A high-accuracy screening method of 44 cephalosporins in meat using liquid chromatography quadrupole-orbitrap hybrid mass spectrometry. Issue 46 (13th November 2017) - Hong, Yun-He; Xu, Xiu-Li; Li, Wei-Qing; Xu, Bo-Zhou; Wu, Han-Qiu; Cheng, Yan; Chen, Hong; Zhang, Bao-Shan; Zhang, Feng
Abstract : In this study, we report the development of a screening method for highly accurate and sensitive analysis of 44 cephalosporins in 4 representative meats (pork, beef, chicken, and mutton). Abstract : In this study, we report the development of a screening method for highly accurate and sensitive analysis of 44 cephalosporins in 4 representative meats (pork, beef, chicken, and mutton). The approach is based on liquid chromatography quadrupole-orbitrap hybrid high resolution mass spectrometry (LC-Q-Orbitrap, HRMS). Highly accurate identification markers of cephalosporins were obtained to have a tool for the detection of non-target or even unknown cephalosporins. Optimal chromatographic separation was studied, and Ascentis C8 column was chosen after comparing several different column materials and mobile phases. A simple sample treatment method consisting of extraction with a mixture of acetonitrile and water followed by solid-phase extraction (SPE) with a PRiME HLB cartridge was developed. The methodology was validated in accordance with the Commission Decision 2002/657/EC by evaluating the following required parameters: linearity, accuracy, repeatability, decision limit (CCα), and detection capability (CCβ). For the matrices studied herein, the recovery rates ranged from 69.2% to 129.0% with the inter- and intra-day variability under 15%. The CCα and CCβ were determined according to maximum residue limit (MRL) or minimum required performance limit (MRPL) when established. The method has been successfully applied to meat samples purchased from the local market, and ceftazidime, which has not yet been considered in the current legislation all over the world, has been found in one of these samples.